Psychological Impact Among Physical Therapists during COVID-19 in Western KSA - Mousa Gihan, Salem Mohamed, Bogari Rana, Yamani Samarah, Al Mazni Waad, Al Sulami Alanoud, Al Sharif Bashyir, Yalli Shatha. Hawsawi Ghada, Kalantan Batool, Faraj Jude, Alqurashi Asma (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 pandemic exposed health care providers such as physiotherapists to psychological disorders as depression and anxiety. Purpose: the purpose of this study was to determine the prevalence of psychological impact among physical therapists during COVID-19 in western Kingdom of Saudi Arabia (KSA). Methods: Researchers performed a cross sectional survey-based study targeting physiotherapists in western KSA during the COVID-19 pandemic by using an online questionnaire. The questionnaire composed of three parts personal, occupational, and psychological. One hundred and ten Physical therapists replied who were working at 18 public and health hospitals of the Western region of KSA providing direct care for patients during the COVID-19 pandemic. Data analysis: Descriptive statistics of mean, standard deviation and percentage were utilized in presenting the subjects characteristics and collected data. Chi-square statistics was utilized to examine psychological injury with subject characteristics. The level of significance was set at p < 0.05 for all tests through the statistical package (SPSS) version 25. Result: One hundred and ten physiotherapists [(60%) females and (40%) males] participated in this study. The results showed that male physiotherapists (63.69%) had higher frequency of psychological disorders in comparison with female physiotherapists (40.9%). Conclusion: The COVID-19 pandemic had a bad effect on psychological aspect of physiotherapists in western KSA.